The Relationship between Career Perception and Career Development and Job Satisfaction of the Indonesian National Police (Polri) at the Yogyakarta Regional Police (Polda Jogjakarta) - Rahmadsyah Lubis; Didit Bambang Wibowo Saputro (Transpublika Publisher, 2026)
This research is motivated by the need to improve job satisfaction among Indonesian National Police (Polri) members to support organizational performance, professionalism, and public trust. A deeper comprehension of the elements affecting members' job satisfaction, especially career risk perception and career development, is necessary due to organizational transformation, professionalism demands, and career development relationships. Hence, this study analyzes the relationship between career perception and career development toward job satisfaction among police members at the Yogyakarta Regional Police. A quantitative approach was employed via a questionnaire survey distributed to 298 respondents using random sampling. Data were collected online using a 5-point Likert scale and analyzed through multiple linear regression to examine both partial and simultaneous effects of independent variables on the dependent variable. Results indicate that career risk perception has a positive and significant relationship with job satisfaction. Career development similarly shows a positive and significant relationship with job satisfaction. These findings suggest that members’ sense of security, stability, and career opportunity positively affect satisfaction, while a planned, transparent, and competency-based career development system fosters work motivation, organizational loyalty, and individual performance. This study implies that optimizing career management and career risk perception should be prioritized in Polri human resource policies, as improved career management is expected to raise job satisfaction, thereby enhancing organizational performance, service quality, and sustained public trust in the institution.